Influence of ionizing radiation on the diffuse reflection spectra of steatite ceramics snc - Ashurov, M.Kh.; Nuritdinov, I.; Dzhumanov, S.; Saidakhmedov, K.Kh. (Karagandy University of the name of acad. E.A. Buketov, 2022)
In this article, the radiation defects induced in steatite ceramics type- SNC- irradiated with high doses of gamma-rays of 60Co source and mixed reactor nо-gamma-irradiation were studied using optical spectroscopy, i.e. diffuse reflection method. An analysis of the results of the diffuse reflection spectra showed that some structural defects are formed under gamma-irradiation. These are oxygen vacancies, unbound oxygen atoms, and E1 - centers (a three-coordinated silicon atom that has captured an electron) in the ultraviolet region of the spectrum. In the visible region of the spectrum, the types of hole centers are different. After decomposing the spectrum of the visible region into Gaussians, it was found that in this region of the spectrum, with no –gamma- irradiation of the reactor, in comparison with gamma-irradiation, various types of hole centers - (O-Me, Me-metal) are additionally formed. The efficiency of creating these structural defects in nо-gamma-reactor irradiated samples was higher compared to gamma irradiated samples
Keywords: steatite ceramics type-SNC; diffuse reflection; gamma-rays; no-gamma-irradiation; V-type hole centers